Pulsed Neutron Logging in the World And in Ukraine: Beggining, Establishment, Present - Петрокушин, Олег Євгенович; Безродна, Ірина Миколаївна (Київський національний університет імені Тараса Шевченка, 2025)
Background. At present, most of the oil and gas fields in Ukraine are depleted, requiring the operator companies in Ukraine to constantly monitor saturation levels and fluid movement withing the reservoirs as these are crucial pieces of information for optimizing and planning further production strategies. Methods. The development and current state of pulsed neutron logging as one of the main methods of monitoring the development of oil and gas fields is described in the paper. Results. The article focuses on the history of the establishment of the pulsed neutron logging, starting from 1949. Further development of the technology includes the creation of neutron generators, improvement of methods and equipment, as well as the appearance of modern multidetector tools. Two main types of pulsed neutron logging are considered: pulsed neutron-neutron logging and pulsed neutron gamma-logging, each has its own advantages and disadvantages. An important stage in the development of pulsed neutron logging was the creation of Sigma logging tools in the 1960s, which measure the neutron capture cross-section and are used to estimate the oil saturation of formation. A significant place in the paper is the analysis of the development of C/O-logging, which was first used in 1971 and determines the ratio of carbon to oxygen for estimating the oil saturation of rocks. The development of multi-detector tools made it possible to acquire logging data through tubing, which significantly expanded the possibilities of pulsed neutron logging. The achievements of domestic geophysicists in the development of pulsed neutron logging in Ukraine are also presented. Modern research is focused on the use of multi-detector tools and MCNP-models for quantitative determination of gas saturation in reservoir rocks. The use of these tools has shown high efficiency in the fields of the Dnieper-Donetsk basin and the Precarpathian depression. Conclusions. The article concludes that pulsed neutron logging plays a key role in the investigation and monitoring of cased oil and gas wells and suggests further steps for the development of this technology in Ukraine, including the introduction of new detectors, an increase in the number of detectors, and the use of MCNP models for more accurate determination of reservoir saturation.

Вступ. Нині більшість нафтових і газових родовищ в Україні виснажені, що вимагає від операторських компаній в Україні постійного моніторингу рівнів насичення та руху флюїду в колекторах, оскільки це є важливою інформацією для оптимізації та планування подальших стратегій видобутку. Метод. Відображено розвиток та сучасний стан імпульсного нейтронного каротажу як одного з основних методів контролю за розробкою нафтових і газових родовищ. Результати. Акцентовано увагу на історії становлення ІНК починаючи з 1949 р. Подальший розвиток технології включає створення генераторів нейтронів, вдосконалення методик і апаратури, а також появу сучасних багатодетекторних приладів. Розглянуто два основні види ІНК: імпульсний нейтрон-нейтронний каротаж (ІННК) і імпульсний нейтронний гамма-каротаж (ІНГК), кожен з яких має свої переваги і недоліки. Важливим етапом розвитку імпульсного нейтронного каротажу стало створення приладів Sigma-каротажу у 1960-х рр., які вимірюють поперечний перетин захоплення нейтронів і використовуються для оцінки нафтонасичення пластів. Значну увагу у статті приділено аналізу розвитку C/O-каротажу, що вперше застосований у 1971 р. і визначає відношення карбону до оксигену для оцінки нафтонасичення порід. Розвиток багатодетекторних приладів дав змогу здійснювати дослідження через насосно-компресорні труби, що значно розширило можливості імпульсного нейтронного каротажу. Також представлено здобутки вітчизняних геофізиків з розвитку імпульсного нейтронного каротажу в Україні. Сучасні дослідження зосереджені на використанні багатодетекторних приладів і MCNP-моделей для кількісного визначення газонасиченості порід-колекторів. Використання цих приладів показало високу ефективність на родовищах Дніпровсько-Донецької западини та Передкарпатського прогину. Висновки. Імпульсний нейтронний каротаж відіграє ключову роль у дослідженні та моніторингу обсаджених нафтогазових свердловин. Запропоновано подальші кроки для розвитку цієї технології в Україні, включаючи впровадження нових детекторів, збільшення кількості детекторів та використання MCNP-моделей для більш точного визначення насиченості пластів.
Імпульсний нейтронний каротаж у світі та в Україні: витоки, становлення, сучасність
Keywords: імпульсний нейтронний каротаж; Sigma-каротаж; С/O-каротаж; MCNP-моделювання; багатодетекторні імпульсні нейтронні прилади; pulsed neutron logging; Sigma-logging; C/O-logging; MCNP-modeling; multi-detector pulsed neutron tools